A philosopher looks at the religious life - Hitz, Zena (United Kingdom : Cambridge University Press, 2023)
"What is happiness? Does life have a meaning? If so, is that meaning available in an ordinary life? The philosopher Zena Hitz confronted these questions head-on when she spent several years living in a Christian religious community. Religious life -- the communal life chosen by monks, nuns, friars, and hermits -- has been a part of global Christianity since earliest times, but many of us struggle to understand what could drive a person to renounce wealth, sex, children, and ambition to live a life of prayer and sacrifice. Hitz's lively and accessible book explores questions about faith, sacrifice, asceticism and happiness through philosophy, stories, and examples from religious life. Drawing on personal experience as well as film, literature, history, biography, and theology, it demystifies an important element of contemporary culture, and provides a picture of human flourishing and happiness which challenges and enriches modern-day life"--
Bibliography : pages 178-183
Keywords: Religion -- Philosophy; Religious life